2016
DOI: 10.1021/acscatal.6b01142
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid/Zn-PPh3 Integrated Porous Organic Polymers Featuring Multifunctional Sites: Highly Active Heterogeneous Catalyst for Cooperative Conversion of CO2 to Cyclic Carbonates

Abstract: A series of ionic liquid (IL), zinc halide (ZnX 2 ), and triphenylphosphine (PPh 3 ) integrated porous organic polymers (POPs) featuring multifunctional sites were afforded through solvothermal synthesis for cyclic carbonate synthesis which utilizes epoxides and carbon dioxide (CO 2 ). Owing to the cooperative effect of ionic liquid and homogeneously distributed Zn-PPh 3 specie, which is probably strengthened by the confined microporous structure and flexible frameworks, these POPs catalysts exhibited high CO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
135
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(138 citation statements)
references
References 80 publications
3
135
0
Order By: Relevance
“…From these results, a possible reaction mechanism using the cycloaddition of propylene oxide with CO 2 as an example is proposed and depicted in Scheme 3 based on the previous literatures [12,13,[34][35][36][37] and the observations in this reactions. At first, the substrate epoxide is activated by TiCl 5 -DMIL@SiO 2 @Fe 3 O 4 to form the complex 1 by the coordination of one TiCl 5 anion with O atom of propylene oxide.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…From these results, a possible reaction mechanism using the cycloaddition of propylene oxide with CO 2 as an example is proposed and depicted in Scheme 3 based on the previous literatures [12,13,[34][35][36][37] and the observations in this reactions. At first, the substrate epoxide is activated by TiCl 5 -DMIL@SiO 2 @Fe 3 O 4 to form the complex 1 by the coordination of one TiCl 5 anion with O atom of propylene oxide.…”
Section: Resultsmentioning
confidence: 94%
“…Examples of their applications in the synthesis of cyclic carbonates from CO 2 and epoxides were reported [33][34][35][36][37]. Although their good catalytic activities in the reaction, they have some problems such as partially ILs wasted and difficulties in separating catalysts from products after the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] Some key processes, to date, using homogenous ionic liquid systems are summarised in Table 1. It is noteworthy, that there have also been a number of solid-supported ionic liquid systems [41][42][43][44][45][46] employed for producing cyclic carbonates. Though they produce high yields of products, these systems also contain undesirable halides and/or metals.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Therefore, POPs possess high specific surface areas, thus enabling their excellent thermal and chemical stability, and the ability to endure harsh reaction conditions. In the recent years, a series of metals that were supported on POPÀ PPh 3 or other derivatives, have been reported, [3] including rhodium, [4] platinum, [5] cobalt, [6] iron, [7] molybdenum, [7] zinc [8] and gold. [3] It was observed that introducing PPh 3 could create high density of ligand sites in the POPs, which led to increased loading stability and capability of the active metals and enhanced capability of catalyst recovery.…”
mentioning
confidence: 99%
“…[9] Recently, Zhang and Zhuang described a synthesis of novel phosphorus-containing hyper-crosslinked porous polymer (HC-TVP) from tris (4-vinylphenyl) phosphane through radical polymerization. [8] In 2017, Zhan and Ding developed a P-doped porous organic polymer and employed it as support and ligand to achieve a novel Pd complex which has shown high efficiency in catalyzing hydrogenation reactions and resulted in high chemoselectivity. [7] Later, Shi and Ma discovered that triazoleÀ gold(I) complex could be anchored into porous organic polymer to enhance the stability and reactivity of gold(I) catalyst.…”
mentioning
confidence: 99%